2012
DOI: 10.1126/science.1225638
|View full text |Cite
|
Sign up to set email alerts
|

Pheromonal Induction of Spatial Learning in Mice

Abstract: Many mammals use scent marking for sexual and competitive advertisement, but little is known about the mechanism by which scents are used to locate mates and competitors. We show that darcin, an involatile protein sex pheromone in male mouse urine, can rapidly condition preference for its remembered location among females and competitor males so that animals prefer to spend time in the site even when scent is absent. Learned spatial preference is conditioned through contact with darcin in a single trial and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
171
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(180 citation statements)
references
References 26 publications
9
171
0
Order By: Relevance
“…More recently, Roberts et al (2012) replicated and expanded these findings by using urine, rather than soiled bedding, as a source of pheromones. Moreover, they demonstrated that darcin, the attractive male sexual pheromone, was the key element that makes male urine rewarding for females: recombinant darcin induces place preference.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
See 2 more Smart Citations
“…More recently, Roberts et al (2012) replicated and expanded these findings by using urine, rather than soiled bedding, as a source of pheromones. Moreover, they demonstrated that darcin, the attractive male sexual pheromone, was the key element that makes male urine rewarding for females: recombinant darcin induces place preference.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…In addition, they also demonstrated that urine volatiles that had become secondary attractors by means of their association with darcin (once again, volatiles were found not to be not primarily attractive) were not able to induce place preference. All these findings strongly suggest that darcin is the main male sexual pheromone of mice, due to its rewarding properties for females, which mediate an interesting type of spatial learning especially adaptive for mate search (see discussion in Roberts et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 88%
See 1 more Smart Citation
“…The pheromone darcin, a major urinary protein, is responsible 49 for female attraction [14]. Male soiled-bedding containing sexual 50 chemosignals [12] or darcin alone [15] induce conditioned place 51 preference in female mice. Similarly, vaginal secretions, containing 52 female sexual chemosignals, induce conditioned place preference 53 in male hamsters [16].…”
mentioning
confidence: 99%
“…Isoform number and sequence are variable between different strains of inbred mice, with many isoforms evolving unique functions. For example, one MUP isoform termed darcin (named after the male protagonist from Pride and Prejudice) increases female mating receptivity, and simultaneously promotes learning of volatile cues in the male's urine [25,26]. In contrast, a different subset of isoforms promote aggression and competition between rival males [27].…”
mentioning
confidence: 99%